EOT11a - Global Empirical Ocean Tide model from multi-mission satellite altimetry, with links to model results - Savcenko, Roman; Bosch, Wolfgang; Dettmering, Denise; Seitz, Florian (Supplement to: Savcenko, Roman; Bosch, Wolfgang (2012): EOT11a - Empirical Ocean Tide Model from Multi-Mission Satellite Altimetry. Deutsches Geodätisches Forschungsinstitut (DGFI), München, 89, 49 pp, hdl:10013/epic.43894.d001, 2012)
EOT11a is a global (E)mpirical (O)cean (T)ide model derived in 2011 by residual analysis of multi-mission satellite (a)ltimeter data. EOT11a includes amplitudes and phases of the main astronomical tides M2, S2, N2, K2, 2N2, O1, K1, P2, and Q1, the non-linear constituent M4, the long period tides Mm and Mf, and the radiational tide S1. Ocean tides as well as loading tides are provided. EOT11a was computed by means of residual tidal analysis of multi-mission altimeter data from TOPEX/Poseidon, ERS-2, ENVISAT, and Jason-1/2, as far as acquired between September 1992 and April 2010. The resolution of 7.5'x7.5' is identical with FES2004 which was used as reference model for the residual tide analysis. The development of EOT11a was funded by the Deutsche Forschungsgemeinschaft (DFG) under grant BO1228/6-2.